The first record of the genus Tanaostigma (Hymenoptera: Tanaostigmatidae) in the Old World, with the description of a new species from India - Gupta, Ankita; Joshi, Sunil (Zootaxa, 2016)
Tanaostigma Howard (Hymenoptera: Tanaostigmatidae) is recorded for the first time in the fauna of the Old World, with T. indica Gupta sp. n. described and illustrated from southern India, reared from Millettia (=Pongamia) pinnata (Fabaceae).